Membrane Remodeling and Matrix Dispersal Intermediates During Mammalian Acrosomal Exocytosis - Leung, Miguel Ricardo; Ravi, Ravi Teja; Gadella, Bart M.; Zeev-Ben-Mordehai, Tzviya (Frontiers in Cell and Developmental Biology, 2021)
To become fertilization-competent, mammalian sperm must undergo a complex series of biochemical and morphological changes in the female reproductive tract. These changes, collectively called capacitation, culminate in the exocytosis of the acrosome, a large vesicle overlying the nucleus. Acrosomal exocytosis is not an all-or-nothing event, but rather a regulated process in which vesicle cargo disperses gradually. However, the structural mechanisms underlying this controlled release remain undefined. In addition, unlike other exocytotic events, fusing membranes are shed as vesicles; the cell thus loses the entire anterior two-thirds of its plasma membrane and yet remains intact while the remaining non-vesiculated plasma membrane becomes fusogenic. Precisely how cell integrity is maintained throughout this drastic vesiculation process is unclear, as is how it ultimately leads to the acquisition of fusion competence. Here, we use cryo-electron tomography to visualize these processes in unfixed, unstained, fully-hydrated sperm. We show that crystalline structures within the acrosome disassemble during capacitation and acrosomal exocytosis, representing a plausible mechanism for gradual dispersal of the acrosomal matrix. We find that the architecture of the sperm head supports an atypical membrane fission-fusion pathway that maintains cell integrity. Finally, we detail how the acrosome reaction transforms both the micron-scale topography and the nano-scale protein landscape of the sperm surface, thus priming the sperm for fertilization.